Advanced water treatment: adsorption - Sillanpaa, Mika (2020)
"In recent decades, industrial activity growth and increasing water usage worldwide have led to the release of various pollutants, such as toxic heavy metals and nutrients, into the aquatic environment. Modified nanocellulose and microcellulose-based adsorption materials have the potential to remove these contaminants from aqueous solutions. Advanced Water Treatment: Adsorption discusses the application of adsorption in water purification. The book reviews research findings consisted of the preparation of five different nano/microcellulose-based adsorbents, their characterization, the study of adsorption kinetics and isotherms, the determination of adsorption mechanisms, and an evaluation of adsorbents' regeneration properties. The book describes modification microfibrillated celluloce (MFC) and the use of succinic anhydride modified mercerized nanocellulose, and aminosilane and hydroxyapatite modified nanostructured MFC for the removal of heavy metals from aqueous solutions. It also describes the use of aminosilane, epoxy and hydroxyapatite modified MFC as a promising alternative for H2S removal from aqueous solutions as well new findings on the adsorption properties of carbonated hydroxyapatite modified MFC as multifunctional adsorbent for the removal of both cations and anions ions from water. The purpose is the delivery of the latest information on advanced water treatment methods to be used by researchers and professionals involved involved in the research and development of water treatment processes. This book is suitable for graduate and advanced undergraduate students, academic researchers and post-docs, manufacturers, consultants, process chemical engineers in the field of Chemical Engineering and Environmental Engineering"--